Effect of previous photoactivation of the adhesive system on the color stability and mechanical properties of resin components in ceramic laminate veneer luting - Strazzi Sahyon, Henrico Badaoui [UNESP]; Chimanski, Afonso; Yoshimura, Humberto Naoyuki; dos Santos, Paulo Henrique [UNESP] (Elsevier, 2018)
Statement of problem: The color stability and mechanical properties of luting agents influence the esthetics and longevity of ceramic restorations. However, studies evaluating the color changes and mechanical properties of luting agents under ceramic laminates activated by using different methods are lacking. Purpose: The purpose of this in vitro study was to evaluate the effects of different modes of photoactivation on the nanohardness and elastic modulus of resin cements and dental adhesives and on the color stability of ceramic laminate veneers. Material and methods: Forty-four lithium disilicate blocks (7×8×0.6 mm) were cemented onto bovine enamel and divided into 4 groups according to the polymerization light (Radii-Cal or Valo) used and the mode of activation of the dental adhesive (no previous photoactivation or previous photoactivation). Single Bond Universal dental adhesive and RelyX Veneer resin cement were used in all experimental groups. Color stability was measured using a UV-2450 ultraviolet-visible spectrophotometer before and after ultraviolet-B artificial accelerated aging (n=8). The nanohardness and the elastic modulus of the adhesive and resin cement were measured using a nanohardness tester (n=3). The color stability and mechanical properties were measured and analyzed using ANOVA and the Tukey least significant difference test (α=.05). Results: No difference in color stability or mechanical properties of the resin cement among the polymerization lights was detected (P>.05). Specimens that underwent previous photoactivation of the adhesive using the Valo polywave unit exhibited higher elastic modulus values than those that did not undergo previous photoactivation (P<.001). Conclusions: The Valo polywave polymerization light improved mechanical properties and color stability more than the Radii-Cal unit. Previous activation of the dental adhesive in the dental enamel with the Valo polywave polymerization light yielded more satisfactory results.